قراءة تحليلية لمكانة الإيرادات الجبائية ضمن الإيرادات العامة في الجزائر-قراءة تحليلية للقوانين المالية خلال الفترة 2014-2021 - بن الطيرش بثينة; خباش زكية; بساس أحمد (جامعة عمار ثليجي الاغواط, 2022)
The aim of our theoretical and analytical study of the subject of an analytical study of the position of tax revenues within public revenues is to address the problem at hand and to determine the extent to which the state’s strategy is successful in reducing the budget deficit to an acceptable level through developing tax revenues and reducing dependency on petroleum tax revenues. Any fluctuation in tax revenues, even petroleum tax revenues, results in fluctuations in public revenues, and tax revenues contribute the largest percentage of contribution compared to petroleum tax revenues, as they outperform them during the study period, and this proves the government’s approach to replacing oil tax with ordinary tax.